2017
DOI: 10.1016/j.plipres.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids and recurrent mood disorders: Phenomenology, mechanisms, and clinical application

Abstract: A body of evidence has implicated dietary deficiency in omega-3 polyunsaturated fatty acids (n-3 PUFA), including eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), in the pathophysiology and etiology of recurrent mood disorders including major depressive disorder (MDD) and bipolar disorder. Cross-national and cross-sectional evidence suggests that greater habitual intake of n-3 PUFA is associated with reduced risk for developing mood symptoms. Meta-analyses provide strong evidence that patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 264 publications
0
31
1
5
Order By: Relevance
“…The PUFA group showed a stronger decline in inflammatory markers (C-reactive protein). Messarmore et al [55] performed a review on PUFA in bipolar disorder and suggested a possible relationship with pathophysiology and pathoetiology [55]. Further reviews also displayed a positive effect on depression [56,57].…”
Section: Other Supplementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PUFA group showed a stronger decline in inflammatory markers (C-reactive protein). Messarmore et al [55] performed a review on PUFA in bipolar disorder and suggested a possible relationship with pathophysiology and pathoetiology [55]. Further reviews also displayed a positive effect on depression [56,57].…”
Section: Other Supplementsmentioning
confidence: 99%
“…As a natural source of PUFA, fish oil, combined with a Mediterranean diet, also had a positive effect on depression [60]. Administration of supplements like DHA, PUFA, and fish oil showed a positive effect therapeutical approach, inflammatory factors, pathophysiology, and pathoetiology of depression [49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Other Supplementsmentioning
confidence: 99%
“…Based on the available data, the DHA depletion in ether lipid‐deficient brains is relatively modest and has arguably less drastic effects than complete deprivation of DHA (or all ω‐3 PUFAs; reviewed in ref. ), as described in many studies investigating the biological relevance of DHA. However, a moderate global DHA deficit and the loss of DHA‐containing plasmalogens as a source of substrates for plasmalogen‐specific phospholipase A2 may be additional puzzle pieces that modulate the pathogenic events under conditions of complete or partial ether lipid deficiency in the nervous system.…”
Section: Molecular Basis and Potential Mechanisms Underlying The Phenmentioning
confidence: 99%
“…46 Μελέτες χορήγησης ω-3-PUFA έχουν δείξει θετικά αποτελέσματα. 47 Σε ασθενείς με διπολική ή καταθλιπτική διαταραχή διαπιστώθηκε σημαντική μείωση της συχνότητας υποτροπών και βελτίωση των καταθλιπτικών συμπτωμάτων, αλλά όχι των συμπτωμάτων μανίας. 48,49 Άλλη μελέτη υποστηρίζει ότι η χορήγηση ω-3-PUFA ωφελεί κυρίως εκείνους τους ασθενείς με κατάθλιψη που εμφανίζουν υψηλά επίπεδα φλεγμονής.…”
Section: συναισθηματικές διαταραχές α μηχανισμοί δράσεωςunclassified